Late Emergence of an Imatinib-Resistant ABL1 Kinase Domain Mutation in a Patient with Chronic Myeloid Leukemia - Crampe, Mireille; Andrews, Claire; Fortune, Anne; Langabeer, Stephen E. (Case Reports in Hematology, 2017)
The introduction of the tyrosine kinase inhibitor (TKI) imatinib has revolutionised the outlook of chronic myeloid leukemia (CML); however, a significant proportion of patients develop resistance through several mechanisms, of which acquisition of ABL1 kinase domain mutations is prevalent. In chronic-phase patients, these mutations become evident early in the disease course. A case is described of a chronic-phase CML patient who achieved a sustained, deep molecular response but who developed an Y253H ABL1 kinase domain mutation nearly nine years after commencing imatinib. Switching therapy to bosutinib resulted in a rapid reachievement of a major molecular response. Long-term TKI treatment impacts on quality of life and late losses of responses are usually due to lack of adherence. This case highlights the requirement for ABL1 kinase domain mutation analysis in those CML patients on long-term imatinib who lost their molecular response, regardless of whether nonadherence is suspected.